PERTANGGUNGJAWABAN PIDANA KORPORASI BERDASARKAN ASAS STRICT LIABILITY (STUDI PEMBAHARUAN HUKUM PIDANA LINGKUNGAN HIDUP) - Kurniawan, Ridho; Sari D, Siti Nurul Intan (Jurnal Yuridis, 2014)
Criminal responsibility adopted by the Indonesian criminal law and environmental law are regulated in Law Number 32/ 2009 on Environmental Protection and Management. The principle of fault liability based complicate law enforcement in the process of criminal evidence. Law Number 32/2009 on Environmental Protection and Management of the Environment has set a strict liability issue but nevertheless the strict liability only obligate to pay compensation in the event a civil lawsuit. Criminal law recognize the strict liability. Strict liability is defined as liability without fault is criminal liability without proof of fault further to the offender. In criminal cases involving corporate environment needs to be applied the principle of strict liability, so that the strict liability can be expanded application not only to the claim for damages in civil cases but can also be done in the legal protection of penal law, is expected with the integration of the law will be able to simplify the process of proving environmental crime by the corporation . This research aims to determine the corporate criminal liability based on the principle of Strict Liability and its implications of the application of strict liability corporation in the process of proving environmental crime.